The Intersection of SGLT2 Inhibitors, Cognitive Impairment, and CKD - Noel, J. Ariana; Hougen, Ingrid; Sood, Manish M. (Frontiers in Neurology, 2022)
Impairment in cognition and decline in kidney function often converge in the aging individual with chronic kidney disease (CKD). Cognitive impairment (CI) may be preventable through modification of health behaviors and risk factors that contribute to the vascular disease burden. CKD patients often have multiple coexisting comorbid conditions contributing to vascular risk. These comorbidities include hypertension, diabetes, cerebrovascular disease, and cardiovascular disease. Emerging evidence suggests that the management and prevention of vascular risk factors and cardiovascular diseases may indirectly contribute to the prevention of CI in CKD. Sodium glucose transport protein 2 inhibitors (SGLT2i) are emerging as the standard of care for selected individuals with CKD, type 2 diabetes (T2DM), and heart failure with rapidly expanding indications being actively investigated. In this narrative review, we examine the intriguing hypothesis that SGLT2i demonstrate potential disease modifying properties in CI among individuals with CKD.